The Effectiveness of Local Wisdom-Based Interactive E-Comics on Learning Outcomes and Motivation in Elementary Students - Gustina Yulia; Weni Yulastri; Rahmatul Hayati (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines the effects of locally wisdom-based interactive e-comics on fifth-grade students' learning outcomes and motivation in fable learning, addressing low achievement and motivation stemming from the dominance of less engaging conventional media. A quasi-experimental method with a non-equivalent control group design was employed. The sample consisted of 37 fifth-grade students from SDN 18 Kampung Dalam (experimental class) and SDN 30 Kampung Dalam (control class). Research instruments included learning outcome tests (pretest and posttest) and a learning motivation questionnaire. Data were analyzed using normality and homogeneity tests and an ANOVA. The findings revealed that the use of interactive e-comics based on local wisdom had a significant effect (p < 0.05) on both learning outcomes and motivation. The experimental class achieved an average posttest score of 93, compared with 83.79 for the control group. The findings revealed a significant difference between the groups (p < 0.05). The experimental class achieved higher posttest scores (93) than the control class (83.79) and showed greater motivation gains (32.78 and 16.06). These results indicate that locally wisdom-based interactive e-comics effectively enhance learning outcomes and motivation, highlighting their potential as an engaging, culturally relevant learning medium in elementary fable instruction.